Perkembangan Sistem Pendidikan di Mesir - Aini Mardiah; Mislaini Mislaini; Khairuna Fitri Lubis (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
The aim of this research is to describe the development of the education system in Egypt. One very attractive educational option for Indonesian students in an Islamic country is education in Egypt. This can be seen from data from the Indonesian Embassy in Egypt, which records that around 8,000 Indonesian students are currently studying there. There are several reasons that cause this. Among them are (1) the quality education system at Al-Azhar, (2) the large number of talaqqi councils, (3) Egypt as the center of the Muslim community in the Middle East, (4) the land of the prophets, (5) affordable living costs, and (6) the many Islamic cultural sites that are often visited by foreign tourists. Another factor that makes education superior in Egypt is the cost of education which is covered by the government, which means education is free. Apart from that, the teaching staff at Al-Azhar are professionals, and the education system implemented is very good.